Impaired Attention and Synaptic Senescence of the Prefrontal Cortex Involves Redox Regulation of NMDA Receptors - Guidi, Michael (J Neurosci, 2015)
Young (3–6 months) and middle-age (10–14 months) rats were trained on the five-choice serial reaction time task. Attention and executive function deficits were apparent in middle-age animals observed as a decrease in choice accuracy, increase in omissions, and increased response latency. The behavioral differences were not due to alterations in sensorimotor function or a diminished motivational state. Electrophysiological characterization of synaptic transmission in slices from the mPFC indicated an age-related decrease in glutamatergic transmission. In particular, a robust decrease in N-methyl-d-aspartate receptor (NMDAR)-mediated synaptic responses in the mPFC was correlated with several measures of attention. The decrease in NMDAR function was due in part to an altered redox state as bath application of the reducing agent, dithiothreitol, increased the NMDAR component of the synaptic response to a greater extent in middle-age animals. Together with previous work indicating that redox state mediates senescent physiology in the hippocampus, the results indicate that redox changes contribute to senescent synaptic function in vulnerable brain regions involved in age-related cognitive decline.